Textiles in air filtration. Issue 4 (2nd October 2017) - Maduna, Lebo; Patnaik, Asis
ABSTRACT: Fossil fuels are a major source of energy although they generate toxic pollutants that cause harm to human beings and the environment. To control these toxic pollutants, various environmental regulations have been imposed and improved filtration technologies have been developed and adopted in response. Multinational agreements have been signed in order to tackle fossil fuel emission as a global problem. Whilst efforts to reduce emissions include the switch from fossil fuel to renewables such as solar, rain and wind, renewables like solar and wind sources and technologies are currently expensive as compared to fossil-fuel technologies. Nonwoven filter media are currently the dominant means by which the fly ash particles that are generated during fossil-fuel combustion are removed; they are widely used because of their high filtration efficiency and low pressure-drop properties. This issue of Textile Progress focuses on the filtration market, the manufacturing techniques used for nonwoven filters, the filtration of fly ash and the mechanisms used to control emissions to meet environmental regulations. Important properties of filter fabrics, their areas of application and disposal issues are discussed and possible reasons are presented for the failure of filters during operation. It addresses the problems faced in achieving effective filtration, not only in fossil fuel power plants but also across a number of other important industries.